In Vitro Propagation and Determination of Dose for Mutation Induction in Torch Ginger (Etlingera Elatior Jack.) - Abu Harirah, Asnita (2002)
Mutation induction has provided an avenue for creating variability in many plant species. Its application has brought new dimension to many horticultural crops including ornamentals where creation of new varieties through conventional breeding and selection has always been difficult, costly and time consuming. The propagation of Etlingera elatior or torch ginger has largely been through the use of suckers with its slow rate of multiplication. Thus, the present study is conducted to develop a protocol for rapid propagation and creation of new and better varieties by combining the techniques of in vitro culture and radiation mutagenesis. In developing the protocol for rapid propagation, in vitro cultures of torch ginger were established by placing shoot tip explants on half and full strength MS medium containing various levels of BAP and NAA each at 1.0, 2.0, 3.0 and 4.0 mg/l and in combinations of both (BAP and NAA). The highest number of shoot multiplication was obtained from treatment with full strength MS medium supplemented with 1.0 mg/l BAP. Cultures in half strength MS medium were not significantly different amongst all treatments. Medium containing BAP alone gave superior results than those with combination of both growth regulators. Generally, the presence of NAA reduced the number of shoots. MS medium supplemented with NAA alone was significantly different in root development except for treatments with full strength MS medium SUpplemented with 4.0 mg/l NAA. The highest number of roots was obtained from treatment in half strength MS medium supplemented with 1.0 mg/l NAA. Irradiation of seeds was done using gamma rays from 60Co source at levels of 10, 20, 30, 40 and 50 Gy at a dose rate of 0.225 Gy / sec. From radiosensitivity test results, a 100% survival rate was recorded from the control and 10 Gy treatments. Treatment at 20 Gy gave survival rate of 600/0. There was no survival from treatments with 30, 40 and 50 Gy.